Efficacy and safety of 1927 nm fractional Thulium fiber laser for the treatment of melasma: a retrospective study of 100 patients. (17th November 2019) - Kurmuş, G.; Tatlıparmak, A.; Aksoy, B.; Koç, E.; Aşiran Serdar, Z.; Ergin, C.
ABSTRACT: Background : Melasma is an acquired hyperpigmentation of the skin that mostly affects areas exposed to the sun. The treatment of melasma can be challenging as it is prone to relapse. Recently, new laser and light-based treatment options have been used; one of these treatment modalities is the 1927 nm fractional Thulium fiber laser. Objective : This study aimed to retrospectively evaluate the efficacy and safety of a 1927 nm fractional Thulium fiber laser for the treatment of melasma. Materials and methods : This study retrospectively evaluated patients who were admitted to the dermatology outpatient clinic between September 2015 and March 2018 and treated with a 1927 nm fractional Thulium fiber laser. The MASI score was used to assess improvements of the lesions. Results : The current study included a total of 100 patients who received 1927 nm fractional Thulium fiber laser treatment. Each patient received two treatments at one month intervals. The mean baseline MASI score was 11.8 ± 6.3, the mean MASI score after the first session was 6.7 ± 4.1, and the mean MASI score after the second session was 3.4 ± 3.8. The differences between these three MASI scores were significant, and the laser treatment had no major side effects. Conclusion : Results of this study indicate that the 1927 nm fractional Thulium fiber laser is a safe and effective treatment option for melasma.